(untitled) (Journal of the College of Basic Education, 2023)
In this paper, an important theorem of equivalence between system of linear Volterra integro-fractional differential equations (LVIFDE’s) with constant coefficients in Caputo derivative scene and the corresponding well-known Volterra integral equation system is demonstrate.